2023
DOI: 10.1029/2022wr033139
|View full text |Cite
|
Sign up to set email alerts
|

Logjam Characteristics as Drivers of Transient Storage in Headwater Streams

Abstract: Logjams in a stream create backwater conditions and locally force water to flow through the streambed, creating zones of transient storage within the surface and subsurface of a stream. We investigate the relative importance of logjam distribution density, logjam permeability, and discharge on transient storage in a simplified experimental channel. We use physical flume experiments in which we inject a salt tracer, monitor fluid conductivity breakthrough curves in surface water, and determine breakthrough‐curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Moreover, the natural helical flow structure of curved river channels may be disrupted, or even prevented from forming, due to the impact of reservoir backwater inundation (Xu et al, 2017; Xu & Bai, 2013). Concurrently, fluctuations in incoming flow at reservoir inlets and outlets may induce reverse slope gradients in meanders, subjecting the flow to additional driving forces (Marshall et al, 2023; Shang et al, 2023). Zhou et al (2014) indicated that a more accurate approach to hydrodynamic models for reservoir sedimentation is to establish a two‐dimensional suspended sediment transport model based on one‐dimensional calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the natural helical flow structure of curved river channels may be disrupted, or even prevented from forming, due to the impact of reservoir backwater inundation (Xu et al, 2017; Xu & Bai, 2013). Concurrently, fluctuations in incoming flow at reservoir inlets and outlets may induce reverse slope gradients in meanders, subjecting the flow to additional driving forces (Marshall et al, 2023; Shang et al, 2023). Zhou et al (2014) indicated that a more accurate approach to hydrodynamic models for reservoir sedimentation is to establish a two‐dimensional suspended sediment transport model based on one‐dimensional calculations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we calculated the effective permeability of the log jam kj ${k}_{j}$, a parameter that has been used in many numerical simulations (Doughty et al., 2020; Marshall et al., 2023; Xu & Liu, 2017). For the range of conditions used in our study (e.g., ϕj= ${\phi }_{j}=$ 0.42, italicFr= $\mathit{Fr}=$ 0.026 to 0.066), our calculations based on Equation suggest kj= ${k}_{j}=$ (6.7 ± 2.3) × 10 −8 m 2 , as shown in Figure 10b.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, diverse forms of restoration may be most effective at the reach‐ to catchment‐scale if focused on beads. Examples of bead function that can be restored or enhanced by process‐based restoration include promoting flux attenuation and associated reduction in flood peaks (Meentemeyer & Butler, 1999; Wegener et al, 2017); groundwater recharge (Westbrook et al, 2006); sediment and phosphate retention (Wohl et al, 2022; Wohl & Scott, 2017); hyporheic exchange and nitrate uptake (Bellmore & Baxter, 2014; Ensign & Doyle, 2005; Marshall et al, 2023); and greater aquatic and riparian habitat abundance and diversity (Hauer et al, 2016; Hood & Larson, 2014; McClain et al, 2003). Conversely, where floodplain inundation or channel migration may be undesirable because of constraints imposed by property or infrastructure, understanding of naturally occurring sources of hydraulic roughness in strings (e.g., step‐pool sequences formed in large wood or boulders; Chin et al, 2021; Comiti et al, 2009) can be used to restore wood or sediment regimes that may facilitate dissipation of energy during high flows.…”
Section: Using Geomorphic Context To Inform Process‐based Restorationmentioning
confidence: 99%